Exploring hepsin functional genetic variation association with disease specific protein expression in bipolar disorder: Applications of a proteomic informed genomic approach. (December 2017) - Nassan, Malik; Jia, Yun-Fang; Jenkins, Greg; Colby, Colin; Feeder, Scott; Choi, Doo-Sup; Veldic, Marin; McElroy, Susan L.; Bond, David J.; Weinshilboum, Richard; Biernacka, Joanna M.; Frye, Mark A.
Abstract: In a prior discovery study, increased levels of serum Growth Differentiation Factor 15 (GDF15), Hepsin (HPN), and Matrix Metalloproteinase-7 (MMP7) were observed in bipolar depressed patients vs controls. This exploratory post-hoc analysis applied a proteomic-informed genomic research strategy to study the potential functional role of these proteins in bipolar disorder (BP). Utilizing the Genotype-Tissue Expression (GTEx) database to identify cis-acting blood expression quantitative trait loci (cis-eQTLs), five eQTL variants from the HPN gene were analyzed for association with BP cases using genotype data of cases from the discovery study (n = 58) versus healthy controls (n = 777). After adjusting for relevant covariates, we analyzed the relationship between these 5 cis-eQTLs and HPN serum level in the BP cases. All 5 cis-eQTL minor alleles were significantly more frequent in BP cases vs controls [(rs62122114, OR = 1.6, p = 0.02), (rs67003112, OR = 1.6, p = 0.02), (rs4997929, OR = 1.7, p = 0.01), (rs12610663, OR = 1.7, p = 0.01), (rs62122148, OR = 1.7, P = 0.01)]. The minor allele (A) in rs62122114 was significantly associated with increased serum HPN level in BP cases (Beta = 0.12, P = 0.049). However, this same minor allele was associated with reduced gene expression in GTEx controls. These exploratory analyses suggest that genetic variation in/near the gene encoding for hepsin protein may influence risk of bipolar disorder. This genetic variation, at least for the rs62122114-A allele, may have functional impact (i.e. differential expression) as evidenced by serum HPN protein expression. Although limited by small sample size, this study highlights the merits of proteomic informed functional genomic studies as a tool to investigate with greater precision the genetic risk of bipolar disorder and secondary relationships to protein expression recognizing, and encouraging in subsequent studies, high likelihood of epigenetic modification of genetic disease risk. Highlights: We identified genetic variation (rs62122114) in HPN correlating with high HPN level. This finding supports the approach of studying peripheral biomarkers in BP. The applied proteomic informed genomic approach helps identify risk variants of BP.